The use of self-retained, cryopreserved amniotic membrane for the treatment of Sjögren syndrome: a case series - Shafer, Brian M.; Fuerst, Nicole; Massaro-Giordano, Mina; Palladino, Vincent; Givnish, Taylor; Macchi, Ilaria; Sulewski Sr, Michael; Orlin, Stephen; Bunya, Vatinee (Digital Journal of Ophthalmology, 2019)
Purpose To determine whether signs and symptoms of ocular surface disease improve after placement of a self-retained, cryopreserved amniotic membrane (CAM) in patients with Sjögren syndrome (SS). Methods The medical records of SS patients who received a self-retained CAM implant (Prokera or Prokera Slim; TissueTech Inc, Doral, FL) for the treatment of ocular surface disease between August 2012 and August 2016 at a single, large academic institution were reviewed retrospectively. Visual acuity, results of slit-lamp examination of the cornea and conjunctiva, and dry eye symptoms, were evaluated before and after CAM insertion. Results A total of 6 eyes of 6 patients (all female; mean age, 62.5 ± 13.0 years [range, 49-86 years]) were included. All patients were on topical medications at the time of the study and had signs of ocular surface dryness. There were reductions in corneal and/or conjunctival staining in 5 eyes (83%) after the CAM dissolved. All patients who completed therapy (5/5) experienced a relapse in their signs and symptoms within 1 month of removal of the CAM, with an average time to relapse of 24.6 days. Mean follow-up time was 54.5 days. Foreign body sensation and blurred vision were the most common complaints associated with the CAM implant. Conclusions In this small case series, self-retained CAM implantation was found to be beneficial in SS patients with ocular surface disease that is refractory to standard therapies; however, we found that the effects were temporary. Future larger studies are needed to confirm these benefits.